Direitos fundamentais nas relações de trabalho no contexto da sociedade de risco: uma análise da lei 13.467/2017 e seus influxos - Santos, Danilo Lucas de Oliveira (2019)
This dissertation aimed to analyze possible violations of the fundamental rights of Brazilian workers, in view of the recent changes in the legal labor system, which were mainly carried out by Law 13467/17. These changes in the norms that are part of the Brazilian labor legal system were linked to the alleged justification of the need to modernize the normative prescriptions that regulate labor relations, with the purpose of promoting both the competitiveness of Brazilian companies in the market and employability. As an analytical matrix, the fundamentals of critical theory were adopted in regard to the unclogging of some conceptions that adorn the aforementioned law. It was intended, therefore, to counter some ideas that surround the novel legislation as a unique alternative, contextualizing the discussion in the neoliberal model of the society of risk, in the axis of the theory of the one conceived by Ulrich Beck. Some categories of this theory have inspired the reflections of this research, such as the de-scheduling of work, which, in this particular, exhorts that the crisis of the productive model, which characterized the Industrial Revolution, inevitably results in the emergence of new paradigms, flexible; paradigm that denotes to inspire the current changes in Brazilian labor standards. The methodology employed observed the effects of the material vectors with which these new legal prescriptions are confronted, with the aim of revealing some of its implications. In this study, the study was based on a special examination of the current sociolegal structures of labor relations, problematizing the main implications for the fundamental rights of Brazilian workers that underlie these changes in labor standards.